PENGARUH KARAKTERISTIK DEWAN DAN STRUKTUR KEPEMILIKAN TERHADAP LUAS PENGUNGKAPAN SUSTAINABILITY REPORTING - Situmorang, Roniasi; Basuki Hadiprajitno, Paulus Th (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to examine the influence of board characteristics and  ownership structure toward sustainability reporting disclosure which integrated by annual reports for all listed manufacturing company on the Indonesia Stock Exchange in the year 2013-2014. Board characteristicsused in this study are size of commisioner, independent commisioner, size of director, and the existence of female directors, and ownership structure used in this study are public ownership and institusional ownership.            The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (BEI) in the year 2013-2014. Total sample is 212 annual report companies as determined by purposive sampling method. This research analyzes sustainability reporting disclosure in annual reports by the method of content analysis. Data analysis was performed with the classical assumption and hypothesis testing of regression method.            The results of this study indicate that independent commisioner, size of director, and institusional ownership did not have significant influence to the sustainability reporting disclosure. Size of commisioner, the existence of female directors, and public ownership had significant influence to sustainability reporting disclosure.